2015
DOI: 10.7717/peerj.1359
|View full text |Cite
|
Sign up to set email alerts
|

Removal of concentrated sulfamethazine by acclimatized aerobic sludge and possible metabolic products

Abstract: This article examined the biological removal of high concentrated sulfamethazine (SMZ) antibiotics by the acclimatized activated sludge in lab-scale SBRs system. The removal of SMZ was characterized by a quick adsorption and a slow process of biodegradation. The adsorption capacity of activated sludge for SMZ was 44 and 47 µg SMZ/g SS, respectively, with the initial SMZ concentrations of 1 and 2 mg/L. The adsorption process fitted pseudo-second-order kinetic model. In a series of batch studies, with the increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…However, the SMZ, COD, and -N removal efficiencies all had a decreasing trend when the SMZ concentration in the influent increased to 3 mg/L. This phenomenon was similar to Yang et al ( 2015 ) in that SMZ was not completely removed by the acclimatized activated sludge. However, it was lower than the 95.4% removal under 0.1–5 mg/L SMZ during the MBR system (Shi et al, 2018 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, the SMZ, COD, and -N removal efficiencies all had a decreasing trend when the SMZ concentration in the influent increased to 3 mg/L. This phenomenon was similar to Yang et al ( 2015 ) in that SMZ was not completely removed by the acclimatized activated sludge. However, it was lower than the 95.4% removal under 0.1–5 mg/L SMZ during the MBR system (Shi et al, 2018 ).…”
Section: Discussionsupporting
confidence: 86%
“…It was pumped into the reactor continuously at room temperature (25–30°C) for 80 days. The flow rate of the peristaltic pump was 4.25 mL/min to maintain the hydraulic retention time (HRT) of 24 h. The operation process could be generally divided into three phases based on SMZ shocks in the influent, which gradually increased from 0.10 to 1 mg/L and 3 mg/L, according to previous studies (Yang et al, 2015 ; Li et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…54 The sulfamethoxazole (SMX) cluster includes sulfamethazine, sulfadiazine, sulfamethoxazole, and sulfamerazine, all of which contain a sulfonamide functional group and all were reported to undergo sulfonamide hydrolysis (btrule 144) in activated sludge, which is consistent with observations in experiments with bacteria isolated from activated sludge. [55][56][57] Diclofenac (DCL) and mefenamic acid form their own cluster; these two micropollutants are the only micropollutants in the database that contain a 1-amino- Based on this review of predicted and observed biotransformations among these 15 micropollutants (16 when bezafibrate is included, and 221 independent observations), it is reasonable to expect that R% within each of the six micropollutant clusters is determined by the same set of predictors. We performed a GAM and stepwise regression on R% as a response variable with six physicochemical properties and six process parameters as predictor variables for each of the ten imputed datasets for each of the micropollutant clusters.…”
Section: Evaluating R% Values Among Micropollutant Clustersmentioning
confidence: 99%
“…The removal efficiency of sulfamethazine reported by Oliveira et al (2017) was lower than that reported in this study, but both studies showed similar increasing trends in the removal efficiency of sulfamethazine with increased HRTs. Previous studies suggest that sulfonamides are removed mainly by quick adsorption onto the sludge, and subsequent biodegradation in the biological treatment process [35,36]. Thus, the biodegradability in a longer HRT might improve the removal of sulfamethazine.…”
Section: Removal Of Antibioticsmentioning
confidence: 99%